2005
DOI: 10.1002/jmri.20255
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relative forced expiratory volume of one second with dynamic magnetic resonance imaging parameters in healthy subjects and patients with lung cancer

Abstract: Purpose: To assess relative forced expiratory volume in one second (FEV1/vital capacity (VC)) in healthy subjects and patients with a lung tumor using dynamic magnetic resonance imaging (dMRI) parameters. Materials and Methods:In 15 healthy volunteers and 31 patients with a non-small-cell lung carcinoma stage I (NSCLC I), diaphragmatic length change (LE1) and craniocaudal (CC) intrathoracic distance change within one second from maximal inspiration (DE1) were divided by total length change (LE total , DE total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…The obvious dependence of lung motion and tumor mobility on tumor localization recently has been proposed to be due to reduced compliance of the tissue surrounding the tumor [17,[27][28][29]. Unfortunately, compliance itself still is not sufficiently locally quantifiable on the basis of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious dependence of lung motion and tumor mobility on tumor localization recently has been proposed to be due to reduced compliance of the tissue surrounding the tumor [17,[27][28][29]. Unfortunately, compliance itself still is not sufficiently locally quantifiable on the basis of imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] It has been reported that chest wall motion evaluated by MRI is a surrogate marker of pulmonary function tests (PFTs). 11,12 Previous studies using MRI showed fl attening of the diaphragm and its limited and/or paradoxical movement in COPD patients compared with normal subjects. 13,14 MRI can also detect the infl uence of a local lung tumor on chest wall motion.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 MRI can also detect the infl uence of a local lung tumor on chest wall motion. 10,12 We postulated that MRI can visualize slight differences in chest wall motion between predominantly upper and lower emphysema.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic magnetic resonance imaging (dMRI) has been proven to be a reliable tool for visualisation and evaluation of local chest wall movement and respiratory mechanics in healthy volunteers [1][2][3] and patients with lung cancer [4].…”
mentioning
confidence: 99%